Benefits and Challenges of Use of Artificial Intelligence in Oral Health Issues of Pediatric Patients - Kadam, Sandhya J; Guttikonda, Krishna Veni; Guttikonda, Bharat Ram Chowdry (Journal of Orofacial Research, 2025)
Oral health is often disregarded, especially within pediatric populations, due to caregivers’ persistent misconception that primary teeth are transient and will fall out. However, the significance of preserving primary dentition until exfoliation is underestimated, as most individuals remain unaware that primary teeth serve as a critical foundation for the eruption of permanent dentition. Many children do not receive routine oral examinations, leading to inadequate oral hygiene habits and dental caries. Compared to adult patients, gaining the cooperation of young children and their management during dental appointments is challenging. Incorporating artificial intelligence (AI) presents numerous advantages for this patient demographic. AI is progressively becoming a fundamental component of healthcare, wherein machines are programmed to emulate human cognitive functions. Imaging is used as a main resource in AI technology, and it is a cornerstone for dentistry. Visuals from AI can help with diagnosis and treatment, as well as simulate results and predict oral diseases. As every technology may have benefits and challenges to use, AI has its limitations and challenges. Training and education of medical staff may help overcome the challenges and use AI in managing oral issues in pediatric patients. Pediatric dental practices are rapidly integrating the AI movement in oral healthcare. The idea of using AI is to augment the knowledge of clinicians and not to replace them. This article provides an overview of AI technology use, benefits, and challenges in pediatric patients with oral health issues.